2013
DOI: 10.1186/1750-1172-8-11
|View full text |Cite
|
Sign up to set email alerts
|

Compounds that correct F508del-CFTR trafficking can also correct other protein trafficking diseases: an in vitro study using cell lines

Abstract: BackgroundMany genetic diseases are due to defects in protein trafficking where the mutant protein is recognized by the quality control systems, retained in the endoplasmic reticulum (ER), and degraded by the proteasome. In many cases, the mutant protein retains function if it can be trafficked to its proper cellular location. We have identified structurally diverse correctors that restore the trafficking and function of the most common mutation causing cystic fibrosis, F508del-CFTR. Most of these correctors d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 39 publications
1
38
0
Order By: Relevance
“…This is supported by previous work in which latonduine was found to correct trafficking mutations from other trafficking diseases, in particular the sulfonyl urea receptor mutation A116P (Sampson et al, 2013). This in turn suggests commonalities of mechanism in the retention of different misfolded proteins in the ER, which may be overcome by proteostatic modulators.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This is supported by previous work in which latonduine was found to correct trafficking mutations from other trafficking diseases, in particular the sulfonyl urea receptor mutation A116P (Sampson et al, 2013). This in turn suggests commonalities of mechanism in the retention of different misfolded proteins in the ER, which may be overcome by proteostatic modulators.…”
Section: Discussionsupporting
confidence: 81%
“…With a correction response in CFBE cells expressing F508del-CFTR that was 3.2% that of wild-type CFTR, MCG315 is almost 10-fold more potent than the parent molecule latonduine, although MCG315 gave only 35% of the response obtained with VX-809 under the same conditions, which is more potent than many other CFTR correctors (Carlile et al, 2007;Robert et al, 2008;Anjos et al, 2012;Zhang et al, 2012;Sampson et al, 2013). When this is considered in combination with the fact the 10-fold increase in corrector potency was found after studying only seven new analogs, this suggests that the latonduine scaffold and its chemical space should be further explored.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…These include two classes of oral hypoglycemic agents: sulfonylureas and glinides, with tolbutamide and glibenclamide in the former class (13,15) and rapaglinide the latter (14), as well as the anticonvulsant carbamazepine that we reported recently (17,19). Interestingly, these earlier studies found that of Ͼ20 trafficking mutations scattered throughout the SUR1 protein tested, only those located in the TMD0 domain were rescued.…”
Section: Discussionmentioning
confidence: 85%
“…More recently, we identified a novel K ATP channel inhibitor carbamazepine (CBZ), which also rescues trafficking-impaired K ATP channels to the cell surface (17,18). Remarkably, the SUR1 trafficking mutations tested so far that are amenable to rescue by SUs or CBZ are all in TMD0 (13,15,17,19), a region known to mediate functional and physical interactions between SUR1 and Kir6.2 (20 -22). Accordingly, we have found that the rescue effect of GBC and CBZ on TMD0 mutants is dependent on Kir6.2 and that both drugs promote the interaction between Kir6.2 and SUR1 (13,23), suggesting that the pharmacological chaperones work in concert with Kir6.2 during translation and/or folding to overcome the structural defects imposed by the TMD0-SUR1 mutations.…”
mentioning
confidence: 99%